SIMILES AND AMBIGUOUS MEANING IN HEATHER’S SONG LYRICS – CONAN GRAY - A, A. Reskiyani Ma'sum; Nur, Sahril; Abdullah, Ahmad Rizal (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study examines the types of similes in the lyrics of